Intense photon emission induced by fracture of γ–irradiated Dy‐, Tm‐, Sm‐ and Mn‐doped CaSO4 single crystals. (30th April 2012) - Chandra, BP; Tiwari, CS; Sharma, R
ABSTRACT: When an γ‐irradiated Dy‐, Tm‐, Sm‐ or Mn‐doped CaSO4 crystal is impulsively deformed, two peaks appear in the ML intensity versus time curve, whereby the first ML peak is found in the deformation region and the second in the post‐deformation region of the crystals. In this study, intensities Im1 and Im2 corresponding to first and second ML peaks, respectively, increased linearly with an impact velocity v0 of the piston used to deform the crystals, and times tm1 and tm2 corresponding to the first and second ML peaks, respectively, decreased with impact velocity. Total ML intensity initially increased with impact velocity and then reached a saturation value for higher values of impact velocity. ML intensity increased with increasing γ‐doses and size of crystals. Results showed that the electric field produced as a result of charging of newly‐created surfaces caused tunneling of electrons to the valence band of the hole‐trapping centres. The free holes generated moved in the valence band and their subsequent recombination with electron trapping centres released energy, thereby resulting in excitation of luminescent centres. Copyright © 2012 John Wiley & Sons, Ltd.